Antibacterial Activity Test Of Extract, N-Hexane Fraction, Ethyl Acetate And Water Of Kesum Leaves (Polygonum Minus H) Against Escherichia Coli ATCC 25922 Bacteria - Wahana Ayu Saputri; Tatiana Siska Wardani; Anna Fitriawati (International Journal of Health Engineering and Technology, 2026)
Diarrheal disease caused by Escherichia coli is a serious health problem in Indonesia, especially in toddlers, with increasing antibiotic resistance. Kesum leaves (Polygonum minus H.) have antibacterial potential because they contain flavonoids, phenols, alkaloids, and saponins. To evaluate the antibacterial activity of 70% ethanol extract and fractions of n-hexane, ethyl acetate, and kesum leaf water against E. coli ATCC 25922, to identify effective concentrations, and to determine the MIC and MBC of the most active fraction. Laboratory experimental study with 70% ethanol maceration extraction and liquid-liquid fractionation. E. coli ATCC 25922 population, 7 kg of simplex samples from Sambas, West Kalimantan. Instruments include an incubator, SPSS 25. Analysis techniques: disc diffusion, liquid/solid dilution, ANOVA.  The ethyl acetate fraction was the most effective (inhibition zone 12.36 mm, at a concentration of 40%, strong category), followed by the extract (inhibition zone 11.31 mm, at a concentration of 30%, medium category), n-hexane (10.46 mm), water (8.86 mm). MIC and MBC of the ethyl acetate fraction were 30%. The extract and fraction of kesum leaves have moderate to strong antibacterial activity against E. coli ATCC 25922, supporting the development of anti-diarrhea herbal medicine.